How Regional Authorities Act Under Restricted Decentralization: Evidence from the Norwegian Transport Sector - Runde Krogstad, Julie; Dotterud Leiren, Merethe (Scandinavian Journal of Public Administration, 2019)
The literature on decentralization points out that there is a tendency to limit discretion at the local level by, for example, imposing national standards. It is therefore of interest to understand how sub-national authorities act under conditions of political decentralization, which is not followed by a similar delegation of administrative competence. Are sub- national authorities able to make policy changes or do they simply follow the same path as the central state authorities prior to decentralization? Drawing on insights from organisational perspectives, it might be expected that the shift of organisational locus affects policy change. Based on qualitative data, we explore the Norwegian Reform of Government Administration, which transferred the bulk of the national road network to the regional level in 2010. This was a political decentralization reform. The sub-national authorities continued to rely on the national road agency’s competence. Although standards, the professional community in the road agency and limited financial resources hampered the effect of the reform, we find that the regional authorities were able to influence the focus of the road agency towards a more sustainable and holistic regional perspective.